Conciencia democrática e industria editorial en los primeros años de la Transición española : la Biblioteca de divulgación política - Marta Simó Comas (Amnis)
This study highlights the role played by the publishing industry in the creation and dissemination of a new civic and political awareness in the early years of Spain’s Transition to Democracy. After four decades of dictatorship, prohibition and disinformation Spain’s civil population was characterised for the most part by passivity, and its generally favourable attitude towards the restoration of Democracy was uninformed by ideological convictions or a critical consciousness. The position taken by this study is that any map of the road to democracy in Spain therefore has to give due weight to the influence of specific publishers and publishing projects in raising and shaping the political and civic consciousness of the population at large. It focuses on the most significant of these: Biblioteca de divulgación política (1976- 1978). This series was the brainchild of Rosa Regas, under whose La Gaya Ciencia imprint it was produced, and aimed to explain a wide range of political concepts, tendencies, parties, civic institutions, etc. in a format that was readily accessible and intelligible to ordinary Spaniards.